Analysis of Basic Immunization Services during the COVID-19 Pandemic at Public Health Centers in Semarang - Yuliyanti, Suryani; Rifqi, Fathurrahman Maulana; Prasetyo, Rizal Lutfi; Nurhasanah, Elis; Priambada, Ahmada Bagus; Abbas, Pujiati (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The Corona Virus Disease 2019 (COVID-19) pandemic has affected public health services, including routine immunization services. If this condition continues, the national immunization coverage will decrease, thereby potentially increasing the risk of immunization preventable diseases. AIM: This study aims to determine the coverage of complete basic immunization services in Semarang before (December 2019) and during the pandemic (May 2020) and the factors that affect the coverage of complete basic immunization services. METHODS: This study describes complete basic immunization based on data taken in June-August 2021 at three health centers in Semarang. The data used were the number of visits and the type of immunization obtained from the medical records of the Health Center Management Information System. In addition, in-depth interviews were conducted with the person in charge of the immunization program at the Public Health Center (Puskesmas) to determine the influence factors of the immunization coverage. The data from the interviews were then analyzed thematically. RESULTS: There were 3594 infants who received immunization services, consisting of 2401 before the pandemic and 1193 during the pandemic. The average decrease in the number of basic immunization services was 50.31%. The decrease in the number of basic immunization services occurred in all network public health centers with an average of Puskesmas Genuk (−36.63%), Halmahera (−40%), and Pandanaran (−26.35%). The mother’s fear of COVID-19 contagious, service time and patients restrictions by the PHC, and IPV vaccine stock out have reduced the basic vaccination coverage in all public health centers. CONCLUSION: There was a decline in basic immunization coverage during the pandemic, so it is necessary to fulfill basic immunization needs and service inn